PERANCANGAN ALAT PEMECAH KULIT KEMIRI TIPE DOUBLE ROLL DENGAN BAHAN ST37 KAPASITAS 82 KG/JAM - Sir Anderson; Zulhendri Zulhendri; Nasirwan Nasirwan; Ramadani Safitri; Pandu Abdi Salam (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2025)
Candlenut (Aleurites moluccana L. Wild) is an economically valuable plantation commodity in Indonesia; however, post-harvest handling is largely conducted using conventional shelling methods, which are inefficient and often cause seed damage, reducing quality and market value. Previous studies have investigated operational parameters of double roll shellers, such as rotational speed, roll spacing, and hopper width, yet most focused on one or two parameters in isolation, without comprehensively assessing the relationship between production capacity, shelling effectiveness, and kernel quality, nor comparing machine performance with traditional methods used by farmers. This research addresses that gap by designing and evaluating a double roll candlenut sheller made of ST37 steel with a target capacity of 82 kg/hour, considering production capacity, shelling efficiency, and kernel quality simultaneously. The design process included literature review, physical and mechanical characterization of candlenuts, structural and transmission system design, and calculations for power requirements and component safety. Results indicated that the maximum force required to shell two candlenuts simultaneously is 3,418.46 N, with a total machine power of 4,012.80 W (≈5.38 hp); applying a service factor of 1.2, a 6.5 hp gasoline engine was selected. Shafts, pulleys, V-belts, and gears were designed to ensure torque, shear stress, and deflection remain within safe limits. The machine operates at a roll speed of 150 rpm, achieves the targeted production capacity, and reduces kernel damage, thereby increasing the value of candlenuts for farmers. This integrated design approach provides a practical and efficient alternative to conventional shelling methods.